Analisis Persaingan Guest House Di Kota Malang - Bagus Razy Syabandita Hakim (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research is motivated by the development of guest house in Malang which is flourish with various kinds of guest house that emerge with potential that can be developed to advance the guest house industry in Malang. The purpose of this study is to find out how the condition of guest house competition and competitive strategy in facing the competition guest house in Malang. This study used descriptive qualitative method. The results of this study based on the concept of five-force analysis by Michael Porter showed that the competition guest house in Malang is high along with rapid growth accompanied by the potential threats of other products and services such as hotels, apartments, and daily-dorm-rooms-that-can-be-rented with a high purchasing oppurtunities. Furthemore in this study found that the differentiations are weak and ineffective use of oppurtunities. Therefore, guest house in Malang City need to develop product differentiation strategy and control relationship with consumer.Kata Kunci : Guest House, Michael Porter, Five Force, Kota Malang, Strategi